2020
DOI: 10.1080/21691401.2020.1773487
|View full text |Cite
|
Sign up to set email alerts
|

LINC00162 participates in the pathogenesis of diabetic nephropathy via modulating the miR-383/HDAC9 signalling pathway

Abstract: View related articlesView Crossmark data Citing articles: 2 View citing articles LINC00162 participates in the pathogenesis of diabetic nephropathy via modulating the miR-383/HDAC9 signalling pathway

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 24 publications
(26 reference statements)
0
4
0
Order By: Relevance
“…The expression of NR_033515 in the kidney, peripheral blood, urine, and serum is increased compared with the control group [ 19 , 28 ], which is related to renal fibrosis, and enhance expression levels of fibrogenesis-related gene proteins (P38, ASK1, and ASK1), fibronectin and α -SMA [ 19 ]. lncRNA-NR_033515 promotes proliferation, fibrosis, and epithelial-mesenchymal transition in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of NR_033515 in the kidney, peripheral blood, urine, and serum is increased compared with the control group [ 19 , 28 ], which is related to renal fibrosis, and enhance expression levels of fibrogenesis-related gene proteins (P38, ASK1, and ASK1), fibronectin and α -SMA [ 19 ]. lncRNA-NR_033515 promotes proliferation, fibrosis, and epithelial-mesenchymal transition in DKD.…”
Section: Discussionmentioning
confidence: 99%
“…58 LINC00162 promotes the progression of DN through the miR-383/HDAC9 signaling axis. 59 MiR-30a-5p improves the damage of immortalized rat podocytes. 60 In addition, studies have found that miR-485 was significantly reduced in DN patients’ serum, and it can also suppress the proliferation and inflammation of HMCs.…”
Section: Discussionmentioning
confidence: 97%
“…Wang et al [48] showed that HDAC2/4/5 expression were upregulated in the kidneys of streptozotocininduced diabetic rats, diabetic db/db mice, and in kidney biopsies from diabetic patients (41). Another experiment showed that upregulation of HDAC9 was found to mediate podocyte injury and promote glomerulosclerosis in diabetic nephropathy mice (32), while analysis of GEO data also showed that HDAC9 expression was upregulated in renal tissue of diabetic nephropathy patients (42). Experimental rat and mice models of cerebral ischemia reperfusion (I/R) injury demonstrated that HDAC9 contributes to brain microvessel endothelial cell dysfunction (43,44).…”
Section: Discussionmentioning
confidence: 99%